Seasonal variation in ovarian and oestrous activity of tropical Menz sheep as affected by plane of nutrition - Mukasa-Mugerwa, E.; Anindo, D.O.; Lahlou-Kassi, A.; Mutiga, E.R.; Sovani, S. (EDP Sciences, 1993)
Fourty eight mature Ethiopian Menz ewes were used to investigate the effect on nutrition on oestrous and ovarian activity in tropical sheeA control group was fed on hay alone and a high nutrition group received an additional 400g per ewe per d of a concentrate feed providing 263 g crude protein/kg dry matter and 10.5 MJ metabolisable energy/kg dry matter. Half the ewes in each group interacted with harnessed vasectomized rams to detect oestrous, which was also verfied by weekly plasma progesterone assays. Ram presence did not depress feed intake or liveweight gain. The mean percentage of ewes showing oestrus at least once a month was very high and there was a marked reduction in sexual activity from June to September, the wet season. Only 79 percent of ewes cycled in August and the number of heats per ewe per month dropped to 1.3 during this wet season in contrast to 1.9 the rest of year. Ewes came into oestrous 21 times a year with no significant effect of level of nutrition. 22 percent of cycles were short, 56 percent normal, 11 percent long, 8 percent silent or missed and 3 percent represented anoestrus with no major difference due to nutrition level. Individual animal progesterone profiles revealed that ewes failing to show oestrus had experienced increased silent ovulations. Fourty percent of undetected heats were from the same animals. percentIt was concluded that, although Menz ewes are year-round breeders, they experience an apparent reduction in sexual activity from June to September, which appears to be independent of the level of nutrition, but might influence their breeding activity and flock production.